BERMAIN DENGAN ANGKA: MENGGUNAKAN SEMPOA UNTUK MENINGKATKAN MINAT DAN KEMAMPUAN NUMERASI SISWA SD - Oktariana, Putri; Claudes, Juniven; Nivia,; Eko Saputro, Bayu; Setiawan, Dany; Tegar Utomo, Mochamad Hammam; Iriani R. Dewi, Fransisca (Jurnal Bakti Masyarakat Indonesia, 2024)
Numeracy is one of the important mathematical skills to be mastered by students at the Elementary School level. Numeracy includes understanding numbers, arithmetic operations, measurement, and solving mathematical problems. The use of abacus in improving students' numeracy skills is interesting. The purpose of this activity is to evaluate the effectiveness of using abacus in improving students' numeracy skills. The activity was carried out using the Pre Test method, teaching the use of abacus, and Post Test to analyze students' ability to solve math problems. The results showed that there was a significant difference between the lowest and highest scores. The average PreTest score was 68.7, and the average Post Test score was 58.2, which gives an idea of the students' understanding of the abacus subject matter. Although there has not been an increase in the use of the abacus, and it has not fully helped students in counting correctly due to the lack of abacus learning time given to students. Collaboration with leading educators and abacus practitioners contributed to the development of more effective teaching methods. Thus, this article concludes that the use of abacus can be an effective tool in improving students' numeracy skills, but it is not achieving the expected results. One way to solve this problem is to give students more time, more practice, more mentoring, and more organized evaluation ABSTRAK Numerasi merupakan salah satu keterampilan matematika yang penting untuk dikuasai oleh siswa-siswi di tingkat Sekolah Dasar. Numerasi meliputi pemahaman tentang angka, operasi aritmatika, pengukuran, dan pemecahan masalah matematika. Penggunaan sempoa dalam meningkatkan kemampuan numerasi siswa secara menarik. Tujuan dari kegiatan ini adalah untuk mengevaluasi efektivitas penggunaan sempoa dalam meningkatkan kemampuan numerasi siswa. Kegiatan dilakukan dengan metode Pre Test, pengajaran penggunaan sempoa, dan Post Test untuk menganalisis kemampuan peserta didik dalam menyelesaikan soal matematika. Hasil kegiatan menunjukkan bahwa terdapat perbedaan yang nilai yang signifikan antara nilai terendah dan tertinggi. Nilai Pre Test rata-rata 68,7, dan nilai Post Test rata-rata 58,2, yang memberikan gambaran tentang pemahaman siswa terhadap materi pelajaran sempoa. Meskipun belum terdapat peningkatan pada penggunaan sempoa, serta belum sepenuhnya membantu siswa dalam berhitung dengan tepat karena kurangnya waktu pembelajaran sempoa yang diberikan kepada siswa. Kerjasama dengan para pendidik terkemuka dan praktisi sempoa berkontribusi dalam pengembangan metode pengajaran yang lebih efektif. Dengan demikian, artikel ini menyimpulkan bahwa penggunaan sempoa dapat menjadi alat yang efektif dalam meningkatkan kemampuan numerasi siswa, tetapi tidak mencapai hasil yang diharapkan. Salah satu cara untuk menyelesaikan masalah ini adalah dengan memberikan lebih banyak waktu kepada siswa, lebih banyak latihan, lebih banyak pendampingan, dan evaluasi yang lebih terorganisir.